Faktor-faktor risiko yang berpengaruh pada insidensi karsinoma serviks uteri: studi retrospektif di rsup dr. Sardjito 1989-1990 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRAK Carcinoma cervix uteri is the most frequent cancer of female genital. This study compared the Relative Risk (RR) and Odds Ratio (OR) between frequency of married (RR =1.48